English passengers - Kneale, Matthew (London : Penguin Books, 2001)
This novel tells two parallel stories: one of three eccentric Englishmen who set sail for Tasmania to find the garden of Eden; the other of a young Tasmanian aborigine and his tribe, struggling against the invading British, who prove as lethal in their good intentions as in their cruelty.
Keywords: Tasmania -- Fiction; Historical fiction